PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN SISTEM PELAPORAN TERHADAP KINERJA MANAJERIAL APARATUR PEMERINTAH - I Gede Eka Budiastawa; Ni Putu Ayu Kusumawati; Cokorda Gde Bayu Putra (UNHI Press, 2021)
The regional government has the authority to run and control the performance of the apparatus in utilizing the stipulated budget. Local governments must meet the criteria for good governance including, clarity of budget targets, accounting controls and a reporting system that will impact on the managerial performance of government officials. The purpose of this study was to determine the effect of clarity of budget targets, accounting controls and reporting systems on managerial performance of government officials. This research is located in all OPD in Klungkung Regency. The population in this study were all employees at 38 Regional Apparatus Organizations (OPD) in the Klungkung Regency Government, amounting to 4,056 people, using judgment sampling techniques, the number of samples in this study was 114 people. The conclusion in this study is the clarity of budget objectives, accounting control and reporting systems have a significant effect on the managerial performance of the Klungkung OPD apparatus.